Philosophical Review in Disaster Mitigation-Based Science Education - Arfianti, Fina; Suri, Natia Afriana; Festiyed, Festiyed; Asrizal, Asrizal; Diliarosta, Skunda; Helendra, Helendra; Adri, Junil; Putri, Lili Dasa (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
The study of Natural Sciences (IPA) plays a crucial role in building students' scientific knowledge, critical thinking skills, and environmental awareness, especially in Indonesia, which is prone to natural disasters. This research analyzes disaster mitigation-based science education through a philosophical approach encompassing the dimensions of ontology, epistemology, and axiology. The method employed is a literature review of 14 articles relevant to the period from 2016 to 2024. The results indicate that, ontologically, this education emphasizes students' understanding of the interaction between natural phenomena and human activities. Epistemologically, experience-based, simulation, and technology-driven approaches have been shown to enhance disaster literacy and mitigation skills. Axiologically, this education instills values of social responsibility, environmental awareness, and solidarity in facing disasters. This integration supports Education for Sustainable Development (ESD) and fosters a generation that is responsive and adaptive to global challenges, including climate change and disaster risks.